2020
DOI: 10.3389/fpls.2020.00548
|View full text |Cite
|
Sign up to set email alerts
|

Deep Soil Water-Use Determines the Yield Benefit of Long-Cycle Wheat

Abstract: Wheat production in southern Australia is reliant on autumn (April-May) rainfall to germinate seeds and allow timely establishment. Reliance on autumn rainfall can be removed by sowing earlier than currently practiced and using late summer and early autumn rainfall to establish crops, but this requires slower developing cultivars to match life-cycle to seasonal conditions. While slow-developing wheat cultivars sown early in the sowing window (long-cycle), have in some cases increased yield in comparison to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 59 publications
0
11
0
1
Order By: Relevance
“…suggested that this advantage of winter wheat is only pronounced in years with sufficient precipitation to wet the entire soil profile. Flohr et al (2020) demonstrated this experimentally in slow developing spring cultivars, with the added condition that low rainfall is required during the critical period to force reliance on deep stored water.…”
Section: Increased Rooting Depth Compared To Spring Wheat (G × M)mentioning
confidence: 86%
See 1 more Smart Citation
“…suggested that this advantage of winter wheat is only pronounced in years with sufficient precipitation to wet the entire soil profile. Flohr et al (2020) demonstrated this experimentally in slow developing spring cultivars, with the added condition that low rainfall is required during the critical period to force reliance on deep stored water.…”
Section: Increased Rooting Depth Compared To Spring Wheat (G × M)mentioning
confidence: 86%
“…Experiments conducted in Australia by Gomez-Macpherson and Richards (1995) and in reviewed experiments of others (Batten and Khan, 1987;Connor et al, 1992) found that grain yields of slow developing cultivars were equivalent to faster developing cultivars sown later despite similar or greater biomass in early sown cultivars due to a lower harvest index. More recent results in south-eastern Australia have demonstrated that the grain yield of slow developing wheat sown early has been equivalent to that of faster developing cultivars with a similar flowering time but with a lower harvest index (Flohr et al, 2020).…”
Section: Increased Biomass Compared To Spring Wheat (G × M)mentioning
confidence: 99%
“…This means more leaves and potential tillering sites are initiated, and a lengthening of the growing period has the potential to increase water use due to greater rooting depth and thus soil water extraction. It may also increase the proportion of water-use transpired; and transpiration efficiency by allowing more growth during winter when vapour pressure deficit is low ( Flohr et al, 2020 ). All these factors increase dry matter (DM) accumulation, grain number, and thus potential grain yield (GY).…”
Section: Introductionmentioning
confidence: 99%
“…Kirkegaard and Hunt (2010) reported that increases in Australian wheat production have come when genotype (G) and management (M) technologies synergies to form coherent farming systems. The combination of new winter wheat genotypes with earlier establishment has the potential to deliver a new water-limited potential yield increase due to the greater rooting depth and deep soil water extraction (Flohr et al, 2020). Future climates may favor the early sowing × slow-developing cultivar × fallow management synergy for winter wheat production (Hunt et al, 2019).…”
Section: F I G U R Ementioning
confidence: 99%